A review and catalogue to the use of models in enabling the achievement of sustainable development goals (SDG). (15th March 2022) - Aly, Ebrahim; Elsawah, Sondoss; Ryan, Michael J.
Abstract: Sustainable development goals (SDG) represent one of the pillars of the UN's 2030 agenda aiming to secure a more sustainable future for all nations. The 17 goals comprising the SDG framework form a transformative action plan that is designed to help nations achieve a more sustainable future focusing on their environmental, social, and economic systems. Achieving the goals within the designated timeframe, however, entails overcoming multiple challenges related to policy design, resources management, and harnessing the synergies and trade-offs among the goals themselves. Recognizing the vital role modeling and simulation can play in facilitating the achievement of the SDG, this paper provides a review of the academic literature published between 2015 and 2021 relating to the models developed to tackle SDG related issues. The main purpose of this review is to explore the modeling practices related to SDG and to determine how aligned those modeling practices are with the priorities of sustainability science. We developed a multi-dimension classification scheme to categorize the models retrieved from the literature based on their main characteristics focusing on characteristics such as the modeling approach used, model uncertainty treatment, model temporal and spatial scales, and which science priority the model focuses on. The results of this research show that most of the models focused on studying policy changes needed to achieve the SDG and monitoring the progress of the SDG. The results also highlight missing important characteristics in SDG models such as cross-scale treatment and advanced uncertainty treatment. While this research can be valuable in informing modelers about the gaps need to be filled in SDG modeling and facilitates the communication between modelers and policy makers, it can be further extended by including an evaluation for the modeling approaches used in SDG contexts as well as adding more characteristics to the model categorization scheme.